Seroprevalence of Severe Acute Respiratory Syndrome Coronavirus 2 Following the Largest Initial Epidemic Wave in the United States: Findings From New York City, 13 May to 21 July 2020. (9th April 2021) - Pathela, Preeti; Crawley, Addie; Weiss, Don; Maldin, Beth; Cornell, Jennifer; Purdin, Jeff; Schumacher, Pamela K; Marovich, Stacey; Li, Joyce; Daskalakis, Demetre; ,
Abstract: Background: New York City (NYC) was the US epicenter of the spring 2020 coronavirus disease 2019 (COVID-19) pandemic. We present the seroprevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and correlates of seropositivity immediately after the first wave. Methods: From a serosurvey of adult NYC residents (13 May to 21 July 2020), we calculated the prevalence of SARS-CoV-2 antibodies stratified by participant demographics, symptom history, health status, and employment industry. We used multivariable regression models to assess associations between participant characteristics and seropositivity. Results: The seroprevalence among 45 367 participants was 23.6% (95% confidence interval, 23.2%–24.0%). High seroprevalence (>30%) was observed among black and Hispanic individuals, people from high poverty neighborhoods, and people in healthcare or essential worker industry sectors. COVID-19 symptom history was associated with seropositivity (adjusted relative risk, 2.76; 95% confidence interval, 2.65–2.88). Other risk factors included sex, age, race/ethnicity, residential area, employment sector, working outside the home, contact with a COVID-19 case, obesity, and increasing numbers of household members. Conclusions: Based on a large serosurvey in a single US jurisdiction, we estimate that just under one-quarter of NYC adults were infected in the first few months of the COVID-19 epidemic. Given disparities in infection risk, effective interventions for at-risk groups are needed during ongoing transmission. Abstract : A large serosurvey following the first wave of the coronavirus disease 2019 epidemic in New York City found that just under one-quarter of adults were infected. Observed disparities in infection risk highlight needs for ongoing, effective interventions in at-risk groups.